Analysis and Design of User Interface / User Experience on Dynamics University Student Affairs Website Using the Google Design Sprint Method - Atika Wardhani Rustiaria; Tri Sagirani; Erwin Sutomo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
kemahasiswaan.dinamika.ac.id is a website from the student affairs section of the Dynamics University which contains important information for students. According to information from the head of student affairs, the website has never been evaluated for usability and redesign of the appearance of the website based on user needs. To determine user needs, the author has conducted a website usability evaluation questionnaire to determine the level of usability and user pain. Based on the problems obtained, an analysis and design of the user interface / user experience (UI / UX) has been carried out on the Undika student website using the google design sprint method. From the test results, it was obtained the results of statements from respondents stating that the UI / UX design was attractive, it was easy to find out the existence on the website, and the use of colors that was comfortable to use. With these results, it can answer problems based on user's pain. Overall, the implementation of the google design sprint method has resulted in a UI / UX design that suits user needs and answers crucial questions based on the problems obtained from the usability evaluation with the Website usability evaluation.